Coherent many-body exciton in van der Waals antiferromagnet NiPS3 - Kang, Soonmin; Kim, Kangwon; Kim, Beom Hyun; Kim, Jonghyeon; Sim, Kyung Ik; Lee, Jae Ung; Lee, Sungmin; Park, Kisoo; Yun, Seokhwan; Kim, Taehun; Nag, Abhishek; Walters, Andrew; et al. (Nature, 2020)
An exciton is the bosonic quasiparticle of electron–hole pairs bound by the Coulomb interaction1. Bose–Einstein condensation of this exciton state has long been the subject of speculation in various model systems2,3, and examples have been found more recently in optical lattices and two-dimensional materials4–9. Unlike these conventional excitons formed from extended Bloch states4–9, excitonic bound states from intrinsically many-body localized states are rare. Here we show that a spin–orbit-entangled exciton state appears below the Néel temperature of 150 kelvin in NiPS3, an antiferromagnetic van der Waals material. It arises intrinsically from the archetypal many-body states of the Zhang–Rice singlet10,11, and reaches a coherent state assisted by the antiferromagnetic order. Using configuration-interaction theory, we determine the origin of the coherent excitonic excitation to be a transition from a Zhang–Rice triplet to a Zhang–Rice singlet. We combine three spectroscopic tools—resonant inelastic X-ray scattering, photoluminescence and optical absorption—to characterize the exciton and to demonstrate an extremely narrow excitonic linewidth below 50 kelvin. The discovery of the spin–orbit-entangled exciton in antiferromagnetic NiPS3 introduces van der Waals magnets as a platform to study coherent many-body excitons.